Fluorine-rich hydrogarnet, prehnite and pumpellyite in monzodioritic basement of the Rhine Rift Valley produced by in-situ low-grade metamorphism at 200 °C and 5 km depth - Kurt Bucher; Moritz Hofer; Florentin Ladner; Ingrid Stober (Swiss Journal of Geosciences)
Abstract The Basel-1 geothermal deep well has been drilled in 2006 to a final depth of 5 km. The recovered core material from 4.9 km depth shows coarse grained biotite-hornblende quartz-monzodiorite from the Variscan basement. The primary igneous rock is locally altered and contains prehnite, pumpellyite, mica and chlorite as major alteration products. Locally small amounts of hydrogarnet formed from pyrite oxidation and fluorine derived from the alteration of primary F-rich biotite. The local low-grade alteration products are consistent with the in-situ measured temperature of about 200 °C. The assemblage of low-grade minerals formed in distinct zones separated by sharp reaction fronts from the primary monzodiorite. The bulk of the alteration zones may have formed from reaction of the monzodiorite with the pre-drilling formation fluid. However, also the external stimulation fluid rapidly readjusted its composition by reaction with the rock at depth. This follows from the temperature derived from fluid composition thermometers applied to recovered stimulation fluid which is consistent with measured temperatures at depth.